Cover Feature: Catalytic Formation of Cyclic Carbonates using Gallium Aminotrisphenolate Compounds and Comparison to their Aluminium Congeners: A Combined Experimental and Computational Study (ChemCatChem 19/2021). Issue 19 (7th October 2021) - Álvarez‐Miguel, Lucía; Burgoa, Jesús Damián; Mosquera, Marta E. G.; Hamilton, Alex; Whiteoak, Christopher J.
Abstract : The Cover Feature highlights the successful use of gallium aminotrisphenolate compounds as catalysts for the synthesis of cyclic carbonates from CO2 and epoxides. In their Full Paper, L. Álvarez‐Miguel et al. highlight the facile synthesis of the gallium compounds, demonstrate their wide substrate scope when employed as catalysts for cyclic carbonate synthesis and compare the gallium compounds to their aluminium congeners, through both experiments and a detailed DFT study. The results indicate that the gallium compounds are highly active and more so than their aluminium congeners. Overall, the results highlight the potential for the application of gallium‐based catalysts for the synthesis of cyclic carbonates and provide a key example of group 13 catalysts beyond aluminium for this application. More information can be found in the Full Paper by L. Álvarez‐Miguel et al.